2017
DOI: 10.1002/aenm.201701370
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Cases of Efficient Nonfullerene Ternary Organic Solar Cells Enabled by an Effective Morphology Control Method

Abstract: of multijunction architecture increases the absorption breadth of a solar cell device, the difficulty of device fabrication and therefore the cost for large-scale production are significantly raised. To maintain the simplicity of the single junction structure and in the meantime broaden the absorption range of the solar cell, ternary OSCs have been developed where two donors and one acceptor or one donor and two acceptors are blended together to form the active layer. Important advances have been realized for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 87 publications
(346 reference statements)
4
119
0
1
Order By: Relevance
“…[64,65] Concurrently, tuning composition of the ternary blend was found to give rise to a change in the energy of the charge transfer states, which is in turn directly related to V oc . [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This subtle optimization point is also evident in the series of TSC devices studied here. On the other hand, V oc is also highly limited by the intrinsic nonradiative recombination losses, and this issue has recently been rigorously investigated for binary blend systems.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[64,65] Concurrently, tuning composition of the ternary blend was found to give rise to a change in the energy of the charge transfer states, which is in turn directly related to V oc . [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This subtle optimization point is also evident in the series of TSC devices studied here. On the other hand, V oc is also highly limited by the intrinsic nonradiative recombination losses, and this issue has recently been rigorously investigated for binary blend systems.…”
Section: Discussionmentioning
confidence: 87%
“…[16] The second polymer is poly[(5,6-difluoro-2,1,3-benzothiadiazol-4,7diyl)-alt-(3,3′″-di-(2nonyltridecyl)2,2′;5′,2″;5″,2′″-quaterthiophen-5,5′″-diyl)] (PffBT4T-C 9 C 13 ) with a quaterthiophene donor unit and a difluorobenzothiadiazole acceptor unit and it gives high efficiency in binary BHJ solar cells. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] This intriguing morphological changes are highly connected to the electrical properties and device FF. The LBG polymer has enabled the extension of absorption to 900 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that PTB7‐Th can balance the mixing and phase separation due to thermal annealing and thus better regulate the morphology. Yan et al reported an effective way to control the nanomorphology of binary OSCs by the ternary strategy, leading to multiple cases of efficient non‐fullerene TOSCs . They presented three key factors.…”
Section: Recent Progress In Ternary Organic Solar Cellsmentioning
confidence: 99%
“…Figure a shows the chemical structures of used materials, two acceptors have similar chemical structures. The two acceptors with similar chemical structures may prefer to form one alloyed acceptor . As described in Figure b, the used materials exhibit complementary absorption spectra for sufficient photon harvesting of the ternary active layers.…”
Section: Photovoltaic Parameters Of the Binary And Ternary Oscsmentioning
confidence: 99%
“…The interfacial energy (γ MeIC‐MeIC2 ≈ 0.0038 mN m −1 ) between two acceptors is much smaller than those (γ MeIC‐PBT1‐C ≈ 0.2943 mN m −1 and γ MeIC2‐ PBT1‐C ≈ 0.2313 mN m −1 ) of between donor and acceptor. The low interfacial energy between MeIC and MeIC2 is beneficial to form an almost inseparable organic phase, the two acceptors may work well together as one alloyed acceptor in ternary OSCs . The energy levels of used materials and schematic diagram of alloy‐like state are exhibited in Figure b.…”
Section: Photovoltaic Parameters Of the Binary And Ternary Oscsmentioning
confidence: 99%